Factors affecting students choice of secondary schols in Tawi-tawi. - Abduhalim, Ismowel H. (s.n., 1983)
This ex post facto study used a sample of 235 first year students from 15 sample high schools which included 8 schools drawn from among the 15 Mindano State University community high schools; 5 from among the 11 public barangay high schools and vocational high schools and 2 from among the 4 Notre Dame public high schools. The parameters in the school quality model appeared as the best linear combination in determining students' school choice. School policies, particularly those related to retention, admission and fiscal matters combined with teacher quality emerged as the leading determinants of student's choice.